Analisis Komparatif Tingkat Kesejahteraan Petani Kelapa Sawit Swadaya Dengan Petani Kelapa Sawit Plasma di Desa Sebatih Kecamatan Sengah Temila Kabupaten Landak - Susilo; Erlinda Yurisinthae; Shenny Oktoriana (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
There are several types of partnerships in the palm oil industry, including swadaya and plasma, each of which generates different incomes and influences the welfare levels of farmers. Therefore, this study aims to explore the differences in welfare levels between swadaya and plasma palm oil farmers in Sebatih Village. This study uses a descriptive quantitative method with snowball sampling technique for random sample selection. The data obtained were analyzed through household income calculation, food expenditure, measurement of farmers' welfare levels, and ttest. The results show that the welfare level of palm oil farmers in Sebatih Village, Sengah Temila District, both swadaya farmers (14.62%) and plasma farmers (28.89%), falls into the high category, with a significant difference between them (t calculated = 22.80 > t table = 2.23).